Identification of a Mitochondria-Related Gene Signature to Predict the Prognosis in AML - Jiang, Nan; Zhang, Xinzhuo; Chen, Qi; Kantawong, Fahsai; Wan, Shengli; Liu, Jian; Li, Hua; Zhou, Jie; Lu, Bin; Wu, Jianming (Frontiers in Oncology, 2022)
Mitochondria related metabolic reprogramming plays a major role in occurrence, development, drug resistance and recurrence of AML. However, the roles of mitochondria related genes (MRGs) in prognosis and immune microenvironment for AML patients remain largely unknown. In this study, by LASSO Cox regression analysis, 4 MRGs (HPDL, CPT1A, IDH3A and ETFB) signature was established that demonstrated good robustness in TARGET AML datasets. The univariate and multivariate Cox regression analysis both demonstrated the MRG signature was a robust independent prognostic factor in overall survival prediction with high accuracy for AML patients. Based on the risk score calculated by the signature, samples were divided into high- and low-risk groups. Gene set enrichment analysis (GSEA) suggested that the MRG signature are involved in the immune-related pathways. And via immune infiltration analysis and immunosuppressive genes analysis, we found that MRG risk of AML patients were strikingly positive correlated with an immune cells infiltration and expression of critical immune checkpoints, indicating that the poor prognosis might be caused by immunosuppressive TME. In summary, the signature based on MRGs could act as an independent risk factor for predicting the clinical prognosis of AML, also reflect an association with immunosuppressive microenvironment, providing a novel method for AML metabolic and immune therapy based on regulation of mitochondrial function.